Communicating Discovery-Based Research Results to the News: A Real-World Lesson in Science Communication for Undergraduate Students - Julie Torruellas Garcia (American Society for Microbiology, 2018)
Communicating science effectively to the general public is a necessary skill that takes practice. Generally, undergraduate science majors are taught to communicate to other scientists but are not given formal training on how to communicate with a nonscientist. An opportunity to appear on a news segment can be used as a real-world lesson on science communication for your students. This article will describe how to contact a producer to get your class on a news segment, ideas for types of research that may be of interest to the media, and how to practice communicating the results effectively.